Analysis of Putative Hybrid between Anaphalis longifolia and A.javanica (Asteraceae) in Mount Talang, West Sumatra based on Anatomical Characteristics - Fajrina, Anzharni; Mansyurdin,; Syamsuardi, (Makara Journal of Science, 2017)
heputative natural hybrid between Anaphalis longifolia and Anaphalis javanica from Talang Mountain in West Sumatra has been discovered. The aim of this research is to analyze the anatomical characteristics of the leaf and stemto clarify the status of this putative natural hybrid. The anatomical characteristics of leaves and stem were analyzed by making cross sectionsand paradermal sectionsusing Johansen’s method. The results show seven characteristics of this putative natural hybrid (the stomata density, length, width, andlength/width ratio; the number of cortical cell layers, the range of cortex length, and the range of cortex width) that were close to A. longifolia, one characteristic that was close to A. javanica (the structure of palisade), one characteristic that was intermediate (the structure of spongy layer), and one characteristic that was a combination of both of them (the trichome morphotype). All of the foregoing characteristics can be used to support the identification of a natural hybrid of A. longifolia and A. javanica.